2016
DOI: 10.1101/072330
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

GAVIN - Gene-Aware Variant INterpretation for medical sequencing

Abstract: We present Gene-Aware Variant INterpretation (GAVIN), a new method that accurately classifies variants for clinical diagnostic purposes. Classifications are based on gene-specific calibrations of allele frequencies from the ExAC database, likely variant impact using SnpEff, and estimated deleteriousness based on CADD scores for >3000 genes. In a benchmark on 18 clinical gene sets, we achieve a sensitivity of 91.4% and a specificity of 76.9%. This accuracy is unmatched by 12 other tools. We provide GAVIN as an … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…However, other methods such as GAVIN suggest that, for PTEN, CADD Phred scores above 29.3 predict that the variant is damaging, and below 17.33 as benign. Using these criteria, only 13 of the 97 variants were assessed as damaging by this criteria, a significant under-representation of the variants found to be damaging according the wing and HEK assays [76] (Fig 7A). PolyPhen-2 uses a naïve Bayes model whose output is binary, and the scores are derived from the posterior probability.…”
Section: Comparison Of Wing Size Scores To Computational Predictionsmentioning
confidence: 99%
“…However, other methods such as GAVIN suggest that, for PTEN, CADD Phred scores above 29.3 predict that the variant is damaging, and below 17.33 as benign. Using these criteria, only 13 of the 97 variants were assessed as damaging by this criteria, a significant under-representation of the variants found to be damaging according the wing and HEK assays [76] (Fig 7A). PolyPhen-2 uses a naïve Bayes model whose output is binary, and the scores are derived from the posterior probability.…”
Section: Comparison Of Wing Size Scores To Computational Predictionsmentioning
confidence: 99%
“…We first observed that the CADD and SNAP2 scores showed a continuous range and correlated only modestly with MCF10A scores (Pearson's r ¼ 0.4483 and 0.4533, respectively). CADD proposes (but does not recommend) a genome-wide cutoff of 15, above which, a variant is likely to be deleterious (7), although alternative methods such as MSC (38) and GAVIN (39) give a PTENspecific cutoff of 18.97 and 17.33, respectively. Using a lower cutoff of 18.5, only two variants were considered benign according to CADD.…”
Section: Using Lof Scores and Machine Learning To Predict Pathogenicity Of Pten Variantsmentioning
confidence: 99%
“…SNPEff (Geoffroy et al, 2015;van der Velde et al, 2017), an annotation tool that can predict the effects due to variations in the genetic code that might result in amino acid changes, was used to enhance the annotations in the VCF files. Additionally, vcfanno (Pedersen, Layer, & Quinlan, 2016) was used to annotate VCF file with extensive available data resources like the Genome Aggregation Database (gnomAD) (Lek et al, 2016), 1,000 genome (Clarke et al, 2017), Combined Annotation-Dependent Depletion (CADD) (Rentzsch, Witten, Cooper, Shendure, & Kircher, 2018), and GERP (Paila, Chapman, Kirchner, & Quinlan, 2013).…”
Section: Incidence Of Pndmmentioning
confidence: 99%